(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
This study aims to enhancement of heat transfer in double pipe heat exchanger by improving the thermal properties of base fluid which is water by adding AL2O3-Fe2O3 nanoparticles to the water. Al2O3-Fe2O3/water hybrid Nanofluid were examined experimentally and numerically at different flow rates ranging between (3 -7) Lpm at temperature of 25°C in an external tube while there was a hot water at a temperature of 60°C and a flow rate ranged between (3 – 5) Lpm running in the central tube of a double pipe counter heat exchanger. Also, the effect of various concentrations ranged between (0.05, 0.1, 0.15, 0.2, 0.25 and 0.3%) of Al2O3-Fe2O3 nanoparticles dispersed in water on the rate of heat transfer, friction coefficient were verified experimentally and numerically . The ratio of Al2O3-Fe2O3 is 0.5:0.5. The experimental and numerical study indicated that with the rate of heat transfer increases when the concentration of suspended nanoparticles in the base fluid increases , but on the other hand, the skin friction coefficient and pressure drop increases as well with increasing the concentration of nanoparticles. The maximum enhancement in heat transfer for AL2O3-Fe2O3 is about 6 % . The results from the experimental study were largely consistent with the numerical results.